Analysis of the Influence of Online Promotion, Product Packaging and Price on Purchasing Decisions with Price as a Moderating Variable: Study: Home Culinary Industry "Cau Nugget", Bandung City - Firdaus*, Edi; Hurriyati, Ratih; Dirgantari, Dwi Puspo; Murugesu, Karina Devi (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This study aims to find out how online promotions, product packaging and prices affect purchasing decisions for culinary products "Cau Nugget" and to determine the effect of price moderation on online promotions in determining purchasing decisions. This study used a quantitative method involving consumer Instagram followers 'Cau Nugget' as a population and a sample of 121 respondents. The results of the study found that, of the three existing factors, online promotions did not have a significant influence on purchasing decisions. Meanwhile, product packaging and price have a significant effect on purchasing decisions. This study proves that price negatively moderates online promotions on purchasing decisions, as well as being the indicator that has the highest impact on purchasing decisions. Keywords: Online Promotion; Product Packaging; Price; Buying Decision; Home Industry